Fast Design Optimization of Microwave Structures Using Co-Simulation-Based Tuning Space Mapping - Kozie, Slawomir; Bandler, John W. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Tuning space mapping (TSM) expedites efficient design optimization of microwave circuits by replacing sections in the electromagnetic (EM) model with corresponding sections of designable equivalent elements. A key assumption of TSM is that these designable elements can replace their respective EM model sections without introducing significant distortion in the structure’s response. This can be achieved through the co-calibrated ports technique introduced in Sonnet em. Here, we generalize the TSM algorithm. A tuning model is constructed by simulating the EM model sections separately and connecting them with the tuning components through a co-simulation process. This allows us to implement the TSM algorithm with any EM simulator. The response misalignment between the original structure and the tuning model is reduced using classical space mapping. The proposed algorithm is illustrated through the design of two microstrip filters simulated in FEKO.